2008
DOI: 10.1159/000170090
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Head Injury Incidence in New Zealand: A Hospital-Based Study from 1997/1998 to 2003/2004

Abstract: Traumatic brain injury (TBI) is a leading cause of disability and death in young adults. Globally, the incidence of TBI hospitalizations is estimated at 200–300 people per 100,000 annually. Using a national health database, we examined the incidence of TBI-related hospital discharges (including 1-day stays) to New Zealand Hospitals from 1997/1998 to 2003/2004. Crude annual hospital-based incidence rates for the total population ranged from 226.9 per 100,000 in 1998/1999 to a high rate of 349.2 in 2002/2003. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
3
31
1
Order By: Relevance
“…The highest head injury incidence rates in the present review occurred among 0-4 year olds, 15-24 year olds and older adults; this is consistent with previous New Zealand research [5,13] and with findings from other countries indicating that older adults and young children are most affected by TBI [14,15,19,28], as are youths and young adults [14,20]. In studies limited to pediatric populations, 0-4 year olds typically have the highest TBI incidence rates [21,29] and death rates [21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The highest head injury incidence rates in the present review occurred among 0-4 year olds, 15-24 year olds and older adults; this is consistent with previous New Zealand research [5,13] and with findings from other countries indicating that older adults and young children are most affected by TBI [14,15,19,28], as are youths and young adults [14,20]. In studies limited to pediatric populations, 0-4 year olds typically have the highest TBI incidence rates [21,29] and death rates [21].…”
Section: Discussionsupporting
confidence: 92%
“…The overall head injury hospitalization incidence rate in the present review (118 per 100,000/year) is 2-3 times lower than that reported in a New Zealand study of head injury incidence from 1997/1998 to 2003/2004 (227-349 per 100,000), but these figures are not comparable as the previous study included day cases [5]. The population-based BIONIC study currently being conducted in New Zealand will be able to provide better estimates of the incidence of head injury across all levels of severity [13].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Clinical syndromes associated with ACC dysfunction are described as apathy and loss of motivation, including akinetic mutism, and are characterized by a lack of motivation. [35][36][37] Such clinical syndromes are seen in FTLD and may be due to atrophy in the relevant cortical regions as well as circuit dysfunction. [31][32][33] Differential volumetrics of the caudate in subtypes of FTLD may be based on the degree of involvement of the caudate in the neuropathophysiology of the subtype.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Pacific peoples in NZ have a high incidence of head injury and spinal cord impairment (60% attributed to injury). 7,8 Pacific rugby players have been found to be at an increased risk of sustaining injuries compared to players of Māori descent. 9 Qualitative research focused upon injury among Pacific workers in the Manukau manufacturing industry identified high injury reporting rates.…”
mentioning
confidence: 99%